2020
DOI: 10.1111/cmi.13204
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of caspase‐1 in inflammasomes activation and bacterial clearance in S. aureus ‐infected osteoblast‐like MG ‐63 cells

Abstract: Staphylococcus aureus, a versatile Gram-positive bacterium, is the main cause of bone and joint infections (BJI), which are prone to recurrence. The inflammasome is an immune signaling platform that assembles after pathogen recognition. It activates proteases, most notably caspase-1 that proteolytically matures and promotes the secretion of mature IL-1β and IL-18. The role of inflammasomes and caspase-1 in the secretion of mature IL-1β and in the defence of S. aureus-infected osteoblasts has not yet been fully… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 91 publications
0
13
0
Order By: Relevance
“…This evidence suggest that the lack of caspase-1 impairs the ability of osteoblast-like cells to limit S. aureus growth. A drastic increase in the proliferation of internalized bacteria in osteoblastic mutant cells has already been highlighted [62] (Figure 5). In fact, a correlation exists between the lack of caspase-1 activation and a failure in limiting S. aureus replication inside phagocytic cells [99,100].…”
Section: Immune Systemmentioning
confidence: 76%
See 2 more Smart Citations
“…This evidence suggest that the lack of caspase-1 impairs the ability of osteoblast-like cells to limit S. aureus growth. A drastic increase in the proliferation of internalized bacteria in osteoblastic mutant cells has already been highlighted [62] (Figure 5). In fact, a correlation exists between the lack of caspase-1 activation and a failure in limiting S. aureus replication inside phagocytic cells [99,100].…”
Section: Immune Systemmentioning
confidence: 76%
“…This binding leads to the autocatalytic cleavage of caspase-1, the processing of pro-IL-1β and pro-IL-18 and the secretion of mature IL-1β and IL-18, triggering in some cases even an inflammatory form of cell death (pyroptosis) [61]). Recent studies have shown that this also applies to S. aureus and MG-63 cells [62,63].…”
Section: Mg-63 Osteoblast-like Cell Line As An Effective In Vitro Modmentioning
confidence: 86%
See 1 more Smart Citation
“…These toxins, particularly Hla, activate a brisk host response, consisting of IL-1β production [ 22 ]. It has long been appreciated that IL-1β is a critical host factor in the pathogenesis of cutaneous S. aureus infection [ 29 ] and has a major role in S. aureus killing and clearance [ 29 , 30 ]. Mice deficient in IL-1β ( Il1- β −/− ) developed larger lesions with higher bacterial burdens and reduced neutrophil recruitment following subcutaneous injection compared to parental strain mice [ 29 ].…”
Section: Host Responses To Acute Infectionmentioning
confidence: 99%
“…Acute PJI becomes di cult to eradicate in the chronic phase as the causative organisms can form mature bio lms and some organisms may parasitize osteoblasts [7,8]. Thus, eradication of the causative organisms in the acute phase with optimal initial intravenous empirical therapy would increase implant retention rate because the absolute number of causative organisms is at a minimum when the irrigation and debridement surgery is performed.…”
Section: Introductionmentioning
confidence: 99%